AKREDITASI SEBAGAI INSTRUMEN PEMBANGUNAN MUTU MADRASAH (TELAAH KEBIJAKAN DAN REKOMENDASI STRATEGIS) - Frisca Alamanda; Muhammad Syaifudin; Asmuri (STAI Nurul Falah Airmolek, 2025)
This study critically evaluates the policy of madrasah accreditation within the framework of Indonesia’s national education quality assurance system. Employing a qualitative-descriptive method and document analysis, the research explores policy content, implementation challenges, stakeholder responses, and the effectiveness of accreditation as a quality enhancement instrument. Ten major regulations are reviewed, including Law No. 20/2003, GR No. 19/2005, GR No. 32/2013, GR No. 17/2010, MoEC Regulations No. 59/2012 and 13/2018, MoRA Regulation No. 90/2013, MoEC Decrees No. 193/2012 and 1005/2020, and BAN-S/M Decree No. 215/2021 on IASP 2020. The findings reveal that despite regulatory progress, implementation remains administratively driven, lacks contextual responsiveness, and provides insufficient institutional support. A paradigm shift toward a transformative, participatory, and empowerment-based accreditation model is urgently needed.